2021
DOI: 10.3390/ijerph18063286
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Thermal Infrared Imaging-Based Screenings during Pandemic Emergencies

Abstract: Infrared thermal imaging (IRI) is a contact-less technology able to monitor human skin temperature for biomedical applications and in real-life contexts. Its capacity to detect fever was exploited for mass screening during past epidemic emergencies as well as for the current COVID-19 pandemic. However, the only assessment of fever may not be selective for the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection. Hence, novel approaches for IRI data analysis have been investigated. The present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 71 publications
0
34
0
3
Order By: Relevance
“…Even with specific cutoff values and correctional algorithms, the sensitivity for detecting fever ranged from 70% to 93% between studies, indicating other factors may influence measurements. 3 In a controlled study of 92 volunteers, Dzien et al found that in cold environments, infrared body temperature was lowest and varied the most immediately upon entering an establishment, but trended towards normal with time inside. 4 Therefore, we hypothesize that environmental factors account for the discrepancy in reported sensitivities due to a direct effect on infrared temperature measurements.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even with specific cutoff values and correctional algorithms, the sensitivity for detecting fever ranged from 70% to 93% between studies, indicating other factors may influence measurements. 3 In a controlled study of 92 volunteers, Dzien et al found that in cold environments, infrared body temperature was lowest and varied the most immediately upon entering an establishment, but trended towards normal with time inside. 4 Therefore, we hypothesize that environmental factors account for the discrepancy in reported sensitivities due to a direct effect on infrared temperature measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Infrared imaging systems (IRIs) and non-contact IR thermometers (NCITs) have been used for mass screenings during outbreaks of the SARS, Ebola, Dengue, and Influenza H1N1 viruses. 1 , 2 , 3 Across the United States, entry screening procedures for COVID-19 infection have been implemented according to the CDC guidelines, including a brief questionnaire and temperature measurement. There is evidence, however, that screening for fever is inadequate in the detection of infected individuals and preventing spread.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermal detection equipment has been in use since the onset of the COVID-19 pandemic to monitor essential workers as primary prevention for limiting the spread of the SARS-CoV-2 virus ( Aggarwal et al, 2020 ; Huang et al, 2020 ; Ontario-Government, 2020a , 2020b ). Similar mass screening entrance protocols were active during previous global outbreaks, including SARS (2003) and the H1N1 pandemic (2009), to detect fevers at international airports and transit terminals ( Cho & Yoon, 2014 ; McBride & Buikstra, 2010 ; Nishiua & Kamiya, 2011 ; Perpetuini et al, 2021 ; Priest et al, 2011 ). The design of mass screening programs allows for the quick assessment of a large number of people in order to classify them based on the probability that they may present a particular condition of interest ( Aragón-Vargas, 2020 ; Trevethan, 2017 ); in this context, the condition of interest is a fever, typically defined as a temperature above 37.8-38 º C ( Cho & Yoon, 2014 ; Priest et al, 2011 ; Zhou et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In an experiment where participants sat in a cold environment (10 º C, 50% relative humidity) for 20 minutes, then entered a warm chamber (30 º C, 50% relative humidity) and rested on a chair for 30 minutes, underestimations of core body temperature occurred for the first 10 minutes ( Kistemaker et al, 2006 ). To our knowledge, no assessment of the effectiveness of NCITs and IRTs has been reflective of environmental temperatures experienced at Canadian workplaces ( Khaksari et al, 2021 ; Perpetuini et al, 2021 ). Therefore, the purpose of this study was to establish the consistency of these devices for determining the surface temperature of the skin and ear in both a simulated environmental exposure (controlled temperature and humidity) and an actual environmental exposure (uncontrolled temperature and humidity).…”
Section: Introductionmentioning
confidence: 99%